PROBLEMATIK GURU DALAM MENGAJARKAN SISWA DALAM MENULIS CERPEN PADA SISWA KELAS V DI SDN KEDOYA UTARA 09 JAKARTA BARAT: PENELITIAN KUALITATIF - Muhammad Rully Ramadhan; Ezik Firman Syah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Teachers' problematic problems in overcoming students' difficulties in writing short stories, lack of student motivation and interest in writing short stories, many students consider writing short stories to be boring and difficult learning, lack of interesting learning strategies, methods and learning models, lack of understanding of the characteristics of their own students, so it has not created effective learning. This research aims to describe how problematic teachers are in overcoming students' difficulties in writing short stories at SDN Kedoya Utara 09. This research was conducted in classes VA, VB, VC, VD. The method used in this research is a descriptive method with a qualitative approach. Data collection techniques use observation, interviews and documentation. The results of this research show that there are problematic aspects with several findings, such as not knowing the character of the students themselves, the teacher's learning process being too monotonous and only using the lecture method, lack of student interest and student motivation in learning short stories. There are aspects of curriculum change with several findings, such as a lack of understanding in implementing the Merdeka curriculum in the classroom. And there are aspects of teacher competency factors with several findings such as, lack of learning strategies, methods and learning models, teachers lacking mastery of techniques in making short stories, limited time in learning. Keywords: Teacher Problems, Teach Short Story Writing, Writing Short Stories.